2017
DOI: 10.1007/s11523-017-0508-3
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Cancer Stem Cells and Stemness for Community Oncologists

Abstract: Advances in cancer research in the past have led to an evolving understanding of cancer pathogenesis and the development of novel drugs that significantly improve patient outcomes. However, many patients still encounter treatment resistance, recurrence, or metastasis and eventually die from progressing disease. Experimental evidence indicates that a subpopulation of cancer cells, called cancer stem cells (CSCs), possess “stemness” properties similar to normal stem cells, including self-renewal, differentiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 139 publications
(190 reference statements)
3
95
0
1
Order By: Relevance
“…Some studies have also suggested that breast cancer cells could acquire the mesenchymal‐like phenotype via EMT, which leads to an increase in the number of stem cells with self‐renewal and spheroidizing ability . Additionally, a part of cancer cells develops the ability of invasion and metastasis through EMT when leaving the primary tumor, while establishes the critical self‐renewal ability as cancer stem cell . As shown by our results, compared with the shNT control cells, knockdown of XB130 inhibited the spheroidizing ability of stem cells and decreased the proportion of SP + cells in vitro.…”
Section: Discussionsupporting
confidence: 65%
“…Some studies have also suggested that breast cancer cells could acquire the mesenchymal‐like phenotype via EMT, which leads to an increase in the number of stem cells with self‐renewal and spheroidizing ability . Additionally, a part of cancer cells develops the ability of invasion and metastasis through EMT when leaving the primary tumor, while establishes the critical self‐renewal ability as cancer stem cell . As shown by our results, compared with the shNT control cells, knockdown of XB130 inhibited the spheroidizing ability of stem cells and decreased the proportion of SP + cells in vitro.…”
Section: Discussionsupporting
confidence: 65%
“…These observations have stimulated the development of anti-CSC therapeutic strategies (Gupta et al 2009b) often targeting surface markers and/or signaling pathways that are aberrantly activated and contribute to CSC proliferation and/or survival. Some of these therapeutic modalities are currently being tested in preclinical and clinical studies (Chen et al 2013;Lathia and Liu 2017).…”
Section: Implications and Opportunities For Therapymentioning
confidence: 99%
“…CSCs preserve self-renewal and proliferative potential via inhibiting differentiation signaling pathways during cancer initiation and development (Jin, Jin, & Kim, 2017;Lathia & Liu, 2017). Remarkably, the balance between differentiation and self-renewal capabilities of CSCs produces the bulk of heterogeneous tumor mass contributing in aggressive and stemness phenotypes (Lathia & Liu, 2017). Specific gene expression profiles are needed for tumor cell differentiation which are dictated through different signaling pathways, transcription factor activities, as well as epigenetic alterations such as DNA modifications (Jögi, Vaapil, Johansson, & Påhlman, 2012).…”
Section: Introductionmentioning
confidence: 99%